Diversity of parasites from Xenopus laevis (Amphibia: Pipidae) and their seasonal rate of infection in selected habitats in the Limpopo Province, South Africa - Mbokane E. M.; Theron J.; Luus-Powel W. J. (Helminthologia, 2020)
This study determined the diversity and seasonality of parasites species of the African clawed frog, Xenopus laevis (Daudin, 1802), from three localities, namely Modjadjikloof, Mokopane and University of Limpopo, Limpopo Province, South Africa. A total of seven parasite species were collected and identified. They included two nematodes, Camallanus kaapstaadiSouthwell & Kirshner, 1937 and Batrachocamallanus slomei (Southwell & Kirshner, 1937), a monogenean, Protopolystoma xenopodis (Price, 1943), a cestode, Cephalochlamys namaquensis (Cohn, 1906), a protozoan, Trichodina xenopodosFantham, 1924, two digeneans, Progonimodiscus doyeri Ortlepp, 1926 and Dollfuschella rodhainiVercammen-Grandjean, 1960. The most common and abundant parasite species by far were Cm. kaapstaadi, B. slomei and Cp. namaquensis, with Cm. kaapstaadi, B. slomei present in all localities. Trichodina xenopodos was a rare species, only present in host populations from Modjadjiskloof. Modjadjiskloof had the highest species richness (all seven parasite species) followed by Mokopane (five parasite species) and University of Limpopo (3 parasite species). There were also higher infection levels (prevalence and mean intensity) of Cm. kaapstaadi, B. slomei, Cp. namaquensis and Pt. xenopodis in hosts from Modjadjiskloof while Pd. doyeri and D. rodhaini infection levels were greater in Mokopane. The variability between localities shows that parasites with heteroxenous life cycles are more strongly associated with more pristine habitats. The variability in calculated indices (prevalence and mean intensity) also suggests that the occurrence of some of the parasites is affected by season, favouring higher infection rates during summer. This suggests that temperature has a direct role in the reproductive and developmental processes of these parasites. Neither length nor sex had an influence on the prevalence or intensity of parasites.